Prevalence and quality of life in high school pupils with acne in Serbia - Peric, Jelena; Maksimovic, Natasa; Jankovic, Janko; Mijovic, Biljana; Reljic, Vesna; Jankovic, Slavenka (Vojnosanitetski pregled, 2013)
Background/Aim. Acne is a common problem in adolescent children with considerable emotional and psychological effects. The aim of this study was to determine the self-reported prevalence of acne and to assess its impact on the quality of life in high school pupils in Serbia. Methods. The cross-sectional study was conducted in May 2011 in two medical high schools in Serbia. Only pupils who gave a written informed consent to participate in the study (n = 440) were asked to fill in two questionnaires: short demographic questionnaire and Cardiff Acne Disability Index (CADI), a disease-specific questionnaire measuring disability induced by acne. Internal consistency (tested by Cronbach’s alpha) and item-total score correlations (Spearman’s correlation analysis) were used for reliability analyses. Results. The study population consisted of 440 pupils, 281 from Belgrade and 159 from Užice. Among them 371 (84.3%) were girls and 69 (15.7%) boys, with similar sex distribution in Belgrade and Užice. The total mean age of pupils was 16.48 years (SD = 0.55). Out of 440 pupils 228 (51.8%) self-reported their acne. The acne prevalence was significantly higher in pupils from Užice (73.6%) than in those from Belgrade (39.6%). The overall mean CADI score for the whole sample was 2.87 ± 2.74, with the similar quality of life impairment in adolescents from Belgrade and from Užice. The mean Cronbach’s alpha was 0.82. Conclusion. This study shows that the quality of life impairment due to acne is mild for the majority of the affected pupils. The Serbian version of the CADI is a reliable, valid, and valuable tool for assessing the impact of acne on the quality of life. Key words: acne vulgaris; adolescent; shcools; serbia; prevalence; quality of life; questionnaires.